Restoration of Fertility after Removal of Extrauterine Mirena Coil: A Case Report and Review of the Literature - Smriti R. C. Bhatta; Radwan Faraj (Case Reports in Obstetrics and Gynecology)
We present the case of a 27-year-old lady who was seen in the infertility clinic with a history of secondary infertility of a one-year duration. She had a hysteroscopy and Mirena insertion for heavy periods. Coil strings were not found by the GP during first coil check six weeks after insertion. A pelvic ultrasound scan did not show any coil, and it was not investigated further with a possible diagnosis of coil expulsion made. One year following that, she was seen in the infertility clinic. Initial investigations revealed anovulation, and HSG located the coil to be extrauterine. Mirena was removed laparoscopically, and a month following the removal she conceived. She is currently pregnant. This case highlights the effect of extrauterine mirena coils on fertility by possibly causing higher plasma levels of levonorgesterol and resulting suppression of ovulation. Laparoscopic removal of mirena coil can help in restoration of fertility.